Study on aquatic plant species (Salvinia natans, Neptunia oleracea and Hydrilla verticillata) as phytoindicator for nutrient excess - Mohd Latiff, Nur Hanie; Shaharuddin, Ruhul Izzati; Wan Muhamad, Wan Naimatul Asiah; Othman, Rashidi (2012)
Aquatic plants are excellent phytoindicator because they respond to nutrients, light, toxic, contaminants, metals, herbicides, turbidity, water level change and salt. However, the negative impact of excessive nutrients on riverine and palustrine systems, estuaries and coastal waters give a serious global problem. Butrients that arise rapidly from expanding urban areas, agricultural and industrial activities caused a boom in aquatic plant growth. Due to the capabilities of aquatic plants to utilize large amounts of nitrogen and phosphorus and thus remove them from the water; the aim of the research is to study the potential of aquatic plant species to be used as phytoindicator for unhealthy environment such as polluted freshwater bodies. In this study, twenty samples of water were collected each from 3 different localities where Salvinia natans, Beptunia oleracea and Hydrilla verticillata were abundant and dominant. All the water samples were analyzed for nitrite, nitrate, ammonium and phosphate. H. verticillata was found to be the best phytoindicator for phosphate pollutant at highest level whereas S. natans and B. oleracea were observed to be useful phytoindicator for unhealthy environment in fresh water bodies for nitrogen and phosphate contaminants. Therefore, aquatic plant species can be fully utilized as an effective tool to detect excessive nutrients in water bodies that might otherwise be difficult to detect.